1989
DOI: 10.1073/pnas.86.22.9015
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine synaptic complex with pyramidal neurons in primate cerebral cortex.

Abstract: Dopamine (DA)-containing projections to the cerebral cortex are considered to play an important role in cognitive processes. Using a recently developed monoclonal antiserum directed against DA and an antibody directed against tyrosine hydroxylase in combination with Golgi impregnation and electron microscopy, we have observed that DA and tyrosine hydroxylase afferents establish symmetric membrane specializations with the soma, dendritic shafts, and spines of identified pyramidal cells in the prefrontal, cingul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
242
0
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(269 citation statements)
references
References 30 publications
23
242
0
2
Order By: Relevance
“…The majority of dopaminergic terminals synapse on pyramidal neurons, while dopaminergic contacts on nonpyramidal neurons are much less dense and are irregularly distributed (Goldman-Rakic et al, 1989;Krimer et al, 1997;Smiley and Goldman-Rakic, 1993). Consistent with this, our present data show higher levels of COMT mRNA in pyramidal than in small, presumably nonpyramidal neurons.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of dopaminergic terminals synapse on pyramidal neurons, while dopaminergic contacts on nonpyramidal neurons are much less dense and are irregularly distributed (Goldman-Rakic et al, 1989;Krimer et al, 1997;Smiley and Goldman-Rakic, 1993). Consistent with this, our present data show higher levels of COMT mRNA in pyramidal than in small, presumably nonpyramidal neurons.…”
Section: Discussionsupporting
confidence: 90%
“…Previous anatomical studies in monkey (Goldman-Rakic et al, 1989;Krimer et al, 1997;Lewis, 1992;Smiley and Goldman-Rakic, 1993) and human (Akil et al, 1999;Lewis, 1992) brain have demonstrated that dopaminergic projections to DLPFC are highly organized and distributed in a bilaminar manner at high densities in the superficial (I/II) and deep layers (V/VI), whereas the distribution is more uniform in the dorsomedial region of this cortical area. The majority of dopaminergic terminals synapse on pyramidal neurons, while dopaminergic contacts on nonpyramidal neurons are much less dense and are irregularly distributed (Goldman-Rakic et al, 1989;Krimer et al, 1997;Smiley and Goldman-Rakic, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…Some of these monoaminergic fibers seem to project directly to nonpyramidal cells of the cortex and probably influence the activity of GABAergic neurons. For example, GABA neurons in rat medial prefrontal cortex receive direct inputs from dopaminergic fibers (Goldman-Rakic et al 1989;Verney et al 1990;Benes et al 1993). Consistent with this, nonpyramidal cells have been found to express both D1 and D2 receptor binding activities (Vincent et al 1993Davidoff and Benes 1998) or their associated messenger RNAs (Huntley et al 1992).…”
Section: Inputs To Gabaergic Neuronsmentioning
confidence: 99%
“…A significant subpopulation of spines [15] is simultaneously contacted by both dopaminergic and glutamatergic varicosities [15][16], forming the "striatal microcircuit" or "synaptic triad" [17]. Similar DA innervation architecture is also observed in pyramidal neurons in the cortex and hippocampus, and magnocellualar neurons of basolateral amygdale [17,32]. This "triad" architecture can serve as a heterosynaptic co-incidence detector by which activation of the DA terminal selectively influences the simultaneously active converging glutamatergic input at the level of individual spines.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%